UV-LED Assisted Ethanol Sensing Properties of NiO-Modified ZnO Thick Film at Low Temperatures - Do, Duc Tho; Nguyen, Thi Nu; Luong, Huu Phuoc; Vu, Xuan Hien; Dang, Duc Vuong; Nguyen, Duc Chien (Old Journal, 2019)
Sensor based on thick film of ZnO hollow microspheres with average thickness about 200 μm were obtained by spin-coating technique. The surface of the film was modified by NiO through dropwise solution of Ni(NO₃)₂ onto the film to reach mass ratio of Ni(NO₃)₂ to ZnO of 1 %. Subsequently, the obtained film was calcined at 500 °C for 2 h. Upon calcination, Ni(NO₃)₂ would reduce to NiO. Ethanol sensing properties of sensor film were investigated and compared with those of pristine ZnO hollow microspheres. The measurement was carried out under illumination of UV-LED (365 nm, 3 W) at temperatures from 75 °C to 125 °C and ethanol vapor concentration levels 125 to 1500 ppm. The results show that the sensor with NiO-modified surface reaches significantly high response (6.5) toward 1500 ppm of ethanol vapor at 100 °C.